Application of Wavelet Analysis in Detecting Runway Foreign Object Debris - Guo Xiao-jing; Yang Xue-you; Yu Zhi-jing (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Foreign Object Debris (FOD) is dangerous for aircraft safety. And it can be suggested to use image processing technology on the FOD’s detection. Depending on image processing system, a major sub-system in FOD detecting system on the runway, FOD image will be observed efficiently and rapidly with few economy costs and highly accuracy and reliability. The paper analyses the characteristics and principles of wavelet transformation algorithm and applies wavelet theory on FOD’s identification and detection. Identifying the FOD’s shape and marking characteristic point on the runway under poor visual background would be accomplished by programming in MATLAB using wavelet algorithm. The results show that the plan is applicable. Besides that, it brings about profound significance for realizing the real-time detecting on the FOD and testing with more feasibility and efficiency.